Evaluating Tax Reforms in Chile with a CGE Model - Mardones, Cristián (Estudios de Economía, 2016)
This paper makes a quantitative assessment of possible reforms to the Chilean tax system. The simulations are based on a recursive dynamic computable general equilibrium model that is calibrated with the input-output matrix 2003. For each scenario is considered a cut effective rate of value added tax and an increase in the richest quintile’s effective rate of income tax by 20% or 40% respectively. The results of the model are transferred to micro data to analyze the effects disaggregated. Finally, I conclude that cutting the VAT and raising income tax only would generate bounded improvements in poverty and income distribution.